Application of Age-friendly Public Health Care in Quality Service for Elderly at Alak Public Health Center - Yulia Herda Hadjon; Pius Weraman; Rina Waty Sirait (Lontar : Journal of Community Health, 2020)
One of the efforts to utilize health services is determined by the quality of service, which is perceived to be good if it is felt as expected. The age-friendly public health care is a form of proactive service approach for the elderly, to support the improvement of the quality of life and independence of the elderly. The study aimed to analyze the application of the age-friendly public health center program in the quality of services to the elderly at the Alak Public Health Center in Kupang City in 2019. This is quantitative research with a cross-sectional study design. The sample of this research is 99 people by using an accidental sampling technique. Data collection used questionnaires of expectations and service performance 32 items each. The analysis conducted is univariate using Importance Performance Analysis. The results indicate that service quality on tangible dimensions is 96.37% (very qualified), reliability 96.13% (very qualified), responsiveness 97.06% (very qualified), assurance 97.57% (very qualified), and empathy 97.66% (very qualified). There are two aspects of the service that need to be improved, that is the availability of special facilities for the elderly, especially seats, and the time the public health center starts. It is expected that the Alak Public Health Center as an Aged-friendly Public Health Center can pay more attention to the comfort of the waiting room for the elderly and the timeliness of service commencement.